Fecal short-chain fatty acids level and pediatric relapsing nephrotic syndrome - Manoppo, Jeanette Irene Christiene; Yolanda, Natharina; Umboh, Adrian (Indonesian Pediatric Society, 2024)
Background The gut microbiota has a potential role in the development of nephrotic syndrome. Fecal short-chain fatty acid (SCFA) levels are representative of gut microbiota activity. Objective To assess for potential associations of fecal short-chain fatty acid levels in pediatric relapsing nephrotic syndrome. Methods This cross-sectional study was done on patients at the Pediatric Nephrology Subdivision of Prof. Dr. R.D. Kandou General Hospital, a referral hospital in Manado, Indonesia. Subjects were 25 patients aged less than 18 years with nephrotic syndrome (NS). We compared the levels of fecal acetic acid, propionic acid, butyric acid percentage, absolute butyric acid, and total short-chain fatty acid between children with relapsing and non-relapsing NS. A receiver operating characteristic (ROC) curve analysis was conducted to determine the significant SCFA cut-off level to diagnose NS. Results Comparison of fecal SCFAs between relapsing and non-relapsing NS groups showed significantly lower butyric acid percentages, absolute butyric acid level, and total SCFAs levels in the relapsing NS group, but not in acetic acid or propionic acid levels. Further multivariate analysis did not show a significant difference in total SCFA levels between relapsing and non-relapsing NS. Absolute butyric acid level had the strongest association with relapsing NS, with the highest predictive score. The absolute butyric acid cut-off value of 0.85 mg/mL had a high sensitivity (90%) and high specificity (93.3%) for predicting relapsing nephrotic syndrome. Conclusion Fecal acetic acid, propionic acid, and total short-chain fatty acid in stool are not associated with relapsing NS in children. However, fecal butyric acid measurements are inversely associated with relapsing NS.